Knowledge on school bullying and its prevention among secondary school teachers in Jaffna education zone - Narmadha, S.; Kamalarupan, L.; Nithlavarnan, A. (University of Jaffna, 2022)
Bullying among children and adolescents is recognized as a significant global public health problem, as it has serious health consequences and behavioural changes. The prevalence of bullying among school-going adolescents is high (37%) in Sri Lanka according to the global school-based student health survey. Adequate knowledge on school bullying and its prevention helps to identify the risk population early and minimize the severe health consequences. The study aimed to assess the knowledge on school bullying and its prevention among secondary school teachers in the Jaffna education zone. School-based descriptive cross-sectional study was carried out among 425 teachers in the Jaffna education zone from October 2020 to November 2021. Ethical approval was obtained from ERC, Faculty of Medicine, University of Jaffna. Two stage random sampling method was used to select the participants. A self-administered questionnaire was used as google form to collect the data. SPSS (Statistical Package of Social Sciences) version 21 is used to analyze the data and the results were presented in percentages. Among the 376 responses (response rate- 88.9%), age range was from 26 to 59 years with a mean of 42. Majority of them were degree holders (57.5%) and having 6-12 years teaching experience (42%). About 61.7% of them had good knowledge of the prevention of school bullying. However, only 26.6% had overall good knowledge on school bullying. And more than half of the participants (61.2%) had moderate knowledge. Few participants had poor knowledge of school bullying (12.2%) and its prevention (7%). To prevent bullying in schools, most participants recommended conducting programs to develop communication and coping skills among students (98.9%) and encouraging all the students to utilize counselling services (97.9%). The present study revealed that more than half of the teachers have good knowledge on bullying prevention than school bullying; therefore, training/education regarding school bullying should be given to improve their knowledge.
Keywords: School Bullying; Prevention; Teachers; Knowledge; Jaffna